First laboratory-confirmed case of scrub typhus in Shijiazhuang City, Hebei Province - Lu, Huixiu; Li, Jianying; Fan, Rong; Hao, Gaoyuan; Sun, Meilan; Liang, Yunchuan (Frontiers in Microbiology, 2024)
Objective: Defining whether a suspected case was due to scrub typhus through laboratory testing, to understand the prevalence of Scrub typhus in Shijiazhuang City, Hebei Province. . Methods: An epidemiological investigation was conducted on the suspected case, utilizing Weil-Felix test and Indirect Immunofluorescence Assay (IFA) to detect specific antibodies against O. tsutsugamushi in serum specimens. Additionally, PCR amplification of the 56-kDa and groEL genes was performed, followed by constructing a phylogenetic tree to identify the genotype.Results: The acute phase titer of the Weil-Felix test for the case was 1:160, which increased to 1:320 in the recovery phase. IFA assay revealed IgG titers against O. tsutsugamushi of 1:64 in the acute phase and 1:256 in the recovery phase. Sequence alignment of the PCR amplified fragment showed the highest similarity with the O. tsutsugamushi genotype. Kawasaki sequence, ranging from 99.71% to 100.00%. The strain exhibited the closest genetic relationship with the known O. tsutsugamushi Kawasaki genotype.Province, with the identified strain belonging to the Kawasaki genotype, marking the first diagnosis of this strain in the region.